Defining success for survivors of domestic violence: perspectives from survivors and service providers - Mengo, Cecilia (Journal of family violence, 2023)
Purpose: Historically, most research looking to improve services for domestic violence (DV) survivors has been designed based on the existing state of services, rather than using direct input from survivors. Building on this research gap, this study seeks to understand what “success” looks like for a broader and diverse population of survivors and service providers. Specifically, this study explored how survivors of DV, and service providers define “success” for survivors of DV. The researchers purposefully chose to keep the definition of success vague to allow participants to define what success is for themselves. This methodology aligns with the field shifting toward a survivor centered lens. Research questions guiding the study were: (1) How do survivors of DV define success? (2) Do themes for survivor-defined success align with service provider-defined program success? Methods: Interviews and focus groups were conducted with 53 DV survivors and 13 service providers in a Midwestern state. Our study was informed by the Appreciative Inquiry methodology. Data analysis was conducted using constant comparative analysis. Results: Seven themes emerged from the data: (1) acknowledging the process, (2) safety, (3) recognizing abuse, (4) therapeutic outcomes, (5) identity, (6) healing, and (7) achievement. Our findings indicate that survivors and service providers agreed on the major themes that were discussed related to defining success for survivors. Conclusion: These findings can inform programs and services of the outcomes that survivors find truly meaningful and explore how those align with current service provider expectations. The outcomes identified can also be used to develop measures that can assess the impact that programs have on survivors.